Thermal processes improving antibrowning potential of mixed Aloe vera and pineapple core extract solution on browning inhibition of fresh‐cut apples. (1st September 2022) - Takeungwongtrakul, Sirima; Sai‐Ut, Samart; Waraput, Thidarat; Supapvanich, Suriyan
Summary: Aloe vera and pineapple fruit extract have been applied as natural antibrowning agent for fresh‐cut products. The effect of different thermal treatment processes (high‐temperature–short‐time pasteurisation at 80 ± 1 °C for 15 s and sterilisation at 121 ± 1 °C for 20 min) of mixed A. vera and pineapple core extract solution at a ratio of 1:1 (v/v) (AP) on enzymatic browning control of fresh‐cut 'Gala' apples was investigated. Both thermal processes increased the antioxidant activities of AP solution compared to unheated AP solution. Coating of both thermal processed AP solutions alleviated the increased browning incidence of the fresh‐cut apples during storage. Compared to sterilised AP coating, the pasteurised AP coating maintained visual appearance, whiteness index (WI) and L * values as well as inhibited browning incidence due to the prevention of increased a *, b *, Δ E * and browning index (BI) values of fresh‐cut apples during storage. The fresh‐cut apples coated with pasteurised AP had lower total phenolic compounds and polyphenol oxidase activity compared to the samples coated with sterilised AP. These suggested that the suitable thermal process was helpful to enhance antibrowning ability of AP coating agents to control enzymatic browning reaction of fresh‐cut fruits. Abstract : Thermal process improving antibrowning property of mixed Aloe vera + pineapple core extract solution.